Hydrothermally Grown ZnO Nanorods as Promising Materials for Low Cost Electronic Skin. Issue 1 (19th November 2019) - Fraleoni‐Morgera, Alessandro; Cesini, Ilaria; Kumar, Pramod; Oddo, Calogero Maria
Abstract: ZnO nanorods (NRs) are nanomaterials with a wide range of applications (photocatalysis, optoelectronics, catalysis, etc). One peculiar property of ZnO NRs is their piezoelectricity, which opens up a wealth of possibilities in the field of pressure sensors. In fact, thanks also to the recent availability of low cost hydrothermal growth, it is already possible to fabricate flexible, large area, self‐powered, distributed pressure sensors, with a high potential for use in robotics and prosthetics as "electronic skins". This review focuses hence on ZnO NRs grown by the hydrothermal method, with an eye on the relationship between the reaction parameters and the resulting NRs morphology, and on their specific application in pressure sensing in terms of device design and performance. Abstract : Feel the force : ZnO nanorods grown by hydrothermal methods are piezoelectric building blocks for low cost, large area electronic skin. Here, we review recent progress in the field in terms of how the growth parameters impact the morphological aspect of the grown nanorods, and on how effective pressure/force sensors can be fabricated using so‐grown ZnO nanorods on different substrates, with an outlook on possible future developments in the field.